Local delivery of a senolytic drug in ischemia and reperfusion-injured heart attenuates cardiac remodeling and restores impaired cardiac function. (November 2021) - Lee, Ju-Ro; Park, Bong-Woo; Park, Jae-Hyun; Lim, Songhyun; Kwon, Sung Pil; Hwang, Ji-Won; Kim, Hyeok; Park, Hun-Jun; Kim, Byung-Soo
Abstract: Myocardial ischemia-reperfusion (IR) generates stress-induced senescent cells (SISCs) that play an important role in the pathophysiology of adverse cardiac remodeling and heart failure via secretion of pro-inflammatory molecules and matrix-degrading proteases. Thus, removal of senescent cells using a senolytic drug could be a potentially effective treatment. However, clinical studies on cancer treatment with a senolytic drug have revealed that systemic administration of a senolytic drug often causes systemic toxicity. Herein we show for the first time that local delivery of a senolytic drug can effectively treat myocardial IR injury. We found that biodegradable poly(lactic-co-glycolic acid) nanoparticle-based local delivery of a senolytic drug (ABT263-PLGA) successfully eliminated SISCs in the IR-injured rat hearts without systemic toxicity. Consequently, the treatment ameliorated inflammatory responses and attenuated adverse remodeling. Surprisingly, the ABT263-PLGA treatment restored the cardiac function over time, whereas the cardiac function decreased over time in the no treatment group. Mechanistically, the ABT263-PLGA treatment not only markedly reduced the expression of pro-inflammatory molecules and matrix-degrading proteases, but also induced macrophage polarization from the inflammatory phase to the reparative phase via efferocytosis of apoptotic SISCs by macrophages. Therefore, the senolytic strategy with ABT263-PLGA in the early stage of myocardial IR injury may be an effective therapeutic option for myocardial infarction. Statement of Significance: This study describes a local injection of senolytic drug-loaded nanoparticles that selectively kills stress-induced senescent cells (SISCs) in infarcted heart. Removal of SISCs decreases inflammatory cytokines and normal cell death. We firstly revealed that further efferocytosis of apoptotic senescent cells by macrophages restores cardiac function after myocardial ischemia-reperfusion injury. Importantly, a local injection of senolytic drug did not exhibit systemic toxicity, but a systemic injection did. Our findings not only spotlight the basic understanding of therapeutic potential of senolysis in infarcted myocardium, but also pave the way for the further application of senolytic drug for non-aging related diseases. Graphical abstract: Image, graphical abstract